Bimbingan dan Konseling - pertiwi, veronica amalia dwi cahya (Borobudur Counseling Review, 2022)
Abstract The background of this research is that parental support is very important for students, especially for choosing a career, because parental support can give a positive impact on students for their development process, especially in choosing a career. Therefore, this study aims to determine the views of students regarding parental support on career choice at SMK Muhammadiyah 1 Moyudan. This research uses a qualitative approach with a case study method. The subjects of this study is students of class XII SMK Muhammadiyah 1 Moyudan totaling 3 people. Methods of collecting data using interviews and documentation studies. The data analysis used is data reduction, data display, and conclusion drawing or verification. In conducting data validity, researchers used data triangulation. The results of this study illustrate the views of students regarding parental support which plays an important role in the career selection process. The forms of parental support are autonomy support, involvement support and warm or responsive support.